NATIONAL WEALTH ASSESSMENT AND UTILIZATION IN TRANSITION ECONOMIES - J. Martinavičius (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The economy’s power and capacities could be measured using different methodologies and numerous macroindicators. The national wealth definition provides an opportunity to reveal not only accumulated resources, but also exposes a real potential of the country and the path for sustainable development. Wealth measurements for transition countries could show the long term development rationality, comparing national wealth structure and its components for different countries. The two methodologies – National Accounts System and World Bank Measuring of wealth, and the obtained comparison results are discussed in the paper.